Bioavailable gluconate chelated stannous fluoride toothpaste meta-analyses: Effects on dentine hypersensitivity and enamel erosion. (February 2021) - West, Nicola X.; He, Tao; Zou, Yuanshu; DiGennaro, Joe; Biesbrock, Aaron; Davies, Maria
Highlights: Dentine hypersensitivity (DH) and enamel erosion are prevalent oral conditions. A meta-analysis showed DH benefits of 22–142 % for SnF2 toothpaste vs controls. A separate meta-analysis showed 83 % less erosion for SnF2 toothpaste vs controls. Twice-daily use of SnF2 toothpaste should benefit patients prone to DH or erosion. Abstract: Objectives: To compare the effect of bioavailable gluconate-chelated stannous fluoride (SnF2 ) toothpaste with control toothpastes for treatment of dentine hypersensitivity (DH) and enamel erosion. Data and sources: A Procter & Gamble Oral Care archive of clinical studies was reviewed from 2000 to 2020. Eligible studies were Randomised Controlled Trials (RCTs) investigating bioavailable gluconate-chelated SnF2 toothpaste efficacy compared to controls in adult participants measured following tactile (Yeaple force) and/or evaporative stimuli (Schiff score) in-vivo, duration < 2 months (DH); or by erosive toothwear (profilometry) from in-situ samples, duration 10–15 days. Two authors independently assessed eligibility and resolved disagreements by discussion. A meta-analysis was undertaken and Risk of Bias (RoB) assessed using the Cochrane collaboration RoB tool for randomized parallel-group and cross-over trials. Results: Fourteen RCTs (1287 participants) assessed DH relief and Six RCTs (184 participants) enamel erosion protection. For DH SnF2 toothpastes provided a 57 % (evaporative air) and 142 % (tactile) benefit versus negative controls (sodium fluoride/monofluorophosphate, 8 studies; p < 0.001). Compared to positive controls (potassium nitrate or arginine, 6 studies), a 22 % advantage (p = 0.036) was seen for evaporative air. In erosion studies, SnF2 toothpastes provided an 83 % benefit versus control toothpastes (arginine or sodium fluoride; p < 0.001) with a change (95 %CI) in average surface profilometry level (μm) of -2.02(-2.85, -1.20). Conclusions: The use of these bioavailable SnF2 toothpastes, as part of a daily oral hygiene regimen, will provide patients with enamel erosion protection, combined with alleviation of DH pain when present, improving quality of life.